The Relationship of Anemia in Pregnant Woman Trimester III with Neonatorum Asphician Events - Sri Martini (LPPM AN NUUR, 2021)
Background: Maternal mortality in developing countries is related to anemia in pregnancy. Most anemia in pregnancy is caused by iron deficiency and acute bleeding. Delivery outcomes in pregnant women suffering from iron deficiency anemia are 12-28%. During pregnancy, the blood count increases by about 20-30%. Anemia in pregnancy will cause obstruction of blood flow to the uterus, so that oxygen circulation to the fetus is reduced. This disorder can cause hypoxia in the fetus so that during delivery it can cause neonatal asphyxia. Purpose: To determine the relationship between anemia in third trimester pregnant women and the incidence of asphyxia neonatorum. Methods: The type of research used is an analytic survey with a Cross Sectional Survey approach, the sample used is 132 respondents of third trimester pregnant women, with a sampling technique that is Simple Random Sampling. Results: It is known that from 26 respondents who gave birth to anemic asphyxia babies 13 and 13 did not have asphyxia, and 106 respondents were not anemic including 24 asphyxia and 82 did not have asphyxia. From the research results obtained p-value 0.005 > 0.05 so it can be concluded that H0 is rejected and H1 is accepted. Conclusion: There is a relationship between anemia in third trimester pregnant women and the incidence of asphyxia neonatorum